2017
DOI: 10.1097/md.0000000000007773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polysaccharide of dendrobium candidum on proliferation and apoptosis of human corneal epithelial cells in high glucose

Abstract: Background:The aim of the study was to observe the effect of polysaccharide of dendrobium candidum (PDC) and high glucose on proliferation, apoptosis of human corneal epithelial cells (HCEC).Methods:The MTT method was used to screen and take the optimal high-glucose concentration, treatment time, and PDC concentration using HCEC and divide it into 4 groups: control group (C), high glucose group (HG), PDC group, and HG + PDC group. We observed and compared the effect of the 4 groups on HCEC proliferation by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
2
11
0
Order By: Relevance
“…Similar effects were observed in DMF-treated cells; treatments at concentration of 10 μM for 24 h induced the proliferation rate of SIRC of about 15% ( p < 0.05). As reported previously, crystal violet assays showed that exposure to HG reduced SIRC growth rate of about 25, 30 and 35% after 24, 48 and 72 h, respectively, ( p < 0.05, Figure 3 , Panel B), considered as sign of glucose-induced dysfunction [ 45 ]. Such a reduction in cell proliferation was not observed in HM-treated SIRC.…”
Section: Resultssupporting
confidence: 64%
“…Similar effects were observed in DMF-treated cells; treatments at concentration of 10 μM for 24 h induced the proliferation rate of SIRC of about 15% ( p < 0.05). As reported previously, crystal violet assays showed that exposure to HG reduced SIRC growth rate of about 25, 30 and 35% after 24, 48 and 72 h, respectively, ( p < 0.05, Figure 3 , Panel B), considered as sign of glucose-induced dysfunction [ 45 ]. Such a reduction in cell proliferation was not observed in HM-treated SIRC.…”
Section: Resultssupporting
confidence: 64%
“…In addition, they have also been shown to prevent calcium overload and inhibit corneal epithelial cell apoptosis. PDC prevent skin photoaging; therefore, they display protection and repair properties [13][14][15]. However, the effects on human skin fibroblasts under high-glucose conditions are yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium candidum has also been shown to have a potent anticancer effect in vitro (Zhao et al 2014), exhibit anti-inflammatory activities, and exert antimetastatic effects ). The polysaccharides within D. candidum can improve the proliferative activity of human corneal epithelial cells (HCEC) under a high glucose environment and reduce cell apoptosis by regulating the expression of BAX and BAL-2 (Li et al 2017). Dendrobium candidum also showed preventive effects on dry mouth symptoms and constipation in animal models (Xiao et al 2011;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%